2019
DOI: 10.1002/pssr.201900007
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Electrical Properties of MoS2 Field‐Effect Transistors by Dipole Layer Coulombic Interaction With Trap States

Abstract: The large negative threshold voltage is one of major electrical factors hindering potential applications of MoS 2 transistors in low-power circuit systems. Here, a strategy by forming an electric dipole layer on the surface of MoS 2 is presented to optimize the threshold voltage in monolayer polycrystalline MoS 2 field-effect transistors. The electric dipole in an inert nonconjugated polymer, perfluoropolyether (PFPE), can interact with trapped electrons in the MoS 2 active layer and transfer the traps from sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…[ 12 ] The first increase and then decrease of the subthreshold slope may be related to the increase of the SV density and the change of defect type from the isolated SVs to the clustered SVs, respectively. [ 5b,13 ] Lastly, we note the H 2 ‐annealed high‐mobility FET is stable for up to a few months (Figure S4a, Supporting Information), different from pristine 2D transistors. Moreover, healing SVs would also greatly reduce the electrical performance of the monolayer MoS 2 (Figure S4c, Supporting Information).…”
Section: Figurementioning
confidence: 99%
“…[ 12 ] The first increase and then decrease of the subthreshold slope may be related to the increase of the SV density and the change of defect type from the isolated SVs to the clustered SVs, respectively. [ 5b,13 ] Lastly, we note the H 2 ‐annealed high‐mobility FET is stable for up to a few months (Figure S4a, Supporting Information), different from pristine 2D transistors. Moreover, healing SVs would also greatly reduce the electrical performance of the monolayer MoS 2 (Figure S4c, Supporting Information).…”
Section: Figurementioning
confidence: 99%
“…Recently, two-dimensional (2D) transition metal dichalcogenides (TMDs), such as MoS 2 , MoSe 2 , WS 2 , and WSe 2 , have attracted tremendous attention as next-generation semiconductors due to their fascinating electrical and optical properties. The electrical properties of 2D TMD-based field effect transistors can be effectively and nondestructively tuned by coating various organic molecules on their surface due to surface charge-transfer doping or formation of heterostructures. However, many previous reports found that this may result in an increase of both ON and OFF current, severely limiting the signal-to-noise ratio (SNR) when applied to photosensing applications (i.e., phototransistors). An example of such an increase in OFF current after coating organic molecules on a 2D TMD-based transistor is shown in Figure S1. Therefore, the effective application of organic coatings on TMD-based phototransistors dictates that it is necessary to limit potential OFF current increases and act as a light absorption layer to improve the photosensitivity (i.e., SNR) of TMD-based phototransistors.…”
Section: Introductionmentioning
confidence: 99%
“…Threshold voltage (V th ) is a key parameter for thin-film transistors (TFTs), which is widely used to characterize the performance of TFTs, such as bias stress effect and light injury. 1,2 However, differing from metal-oxide semiconductor field-effect transistor (MOSFET), the materials of TFTs are usually ploy-crystalline and amorphous structure, which leads to the different definition and extract methods of V th . Generally, the value of V th extracted by using different methods is various.…”
Section: Introductionmentioning
confidence: 99%
“…For conventional transistors operating in linear mode (V d < V g -V th ), the threshold voltage (V th ) can be obtained by 2…”
Section: Introductionmentioning
confidence: 99%